2012
DOI: 10.1109/tsp.2011.2169408
|View full text |Cite
|
Sign up to set email alerts
|

Reconciling Compressive Sampling Systems for Spectrally Sparse Continuous-Time Signals

Abstract: The Random Demodulator (RD) and the Modulated Wideband Converter (MWC) are two recently proposed compressed sensing (CS) techniques for the acquisition of continuous-time spectrallysparse signals. They extend the standard CS paradigm from sampling discrete, finite dimensional signals to sampling continuous and possibly infinite dimensional ones, and thus establish the ability to capture these signals at sub-Nyquist sampling rates. The RD and the MWC have remarkably similar structures (similar block diagrams), … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(25 citation statements)
references
References 38 publications
(172 reference statements)
1
24
0
Order By: Relevance
“…The goal of the modulator is to alias the spectrum into baseband. The most distinguishing characteristic of the MWC from that of the RD is that the RD has sampling functions that have finite temporal extent but infinite spectral support while the MWC employs sampling functions that have finite spectral support but infinite temporal support [138].…”
Section: Hardware Architecturesmentioning
confidence: 99%
“…The goal of the modulator is to alias the spectrum into baseband. The most distinguishing characteristic of the MWC from that of the RD is that the RD has sampling functions that have finite temporal extent but infinite spectral support while the MWC employs sampling functions that have finite spectral support but infinite temporal support [138].…”
Section: Hardware Architecturesmentioning
confidence: 99%
“…MWC has been considered to be an effective approach for compressed sampling and signal reconstruction with its applications on radar, broadband communication, and cognitive radio spectrum sensing [12][13][14].…”
Section: Wireless Communications and Mobile Computingmentioning
confidence: 99%
“…The compressed sensing holds considerable promise for continuously acquiring signals at a much lower sampling rate than Nyquist while still able to accurately reconstruct signals. Lexa et al [78] proposed a new acquisition system for continuous-time signals whose amplitudes were block sparse, and showed that ''block convolution'' implemented could successfully sample and reconstruct multiband signals. Fig.…”
Section: Measurement Acquisition With Low Sampling Ratementioning
confidence: 99%